Counseling and Supervision Impact on Elderly Tuberculosis Patients’ Medication Compliance - Mamang, Aisah; Anwar, Syamsul; Yunitri, Ninik; Herlinah, Lily (GLOBAL HEALTH SCIENCE GROUP, 2024)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which spreads mainly through the air, especially attacking the lungs but can infect any organ, including the brain, kidneys, bones, and lymph nodes. One factor contributing to non-compliance in TB patients is irregular treatment. If treatment is not consistent, it can lead to drug-resistant germs, prolonging treatment and reducing success. Objective: The aim of this study was to improve medication compliance through evidence-based nurturing practices. Method: This study employed two phases including a systematic review to determine the EBNP and the second phase was the implementation of the EBNP. We gathered the participant using total participant but stricly applied the inclusion and exlcusion criteria. Fifteen elderly aged 63±3.314 years in Karanganya, Sawah Besar, Jakarta Pusat were participated in this study. The data analysis using Jamovi aimed to assess the impact of counseling and medication supervision on medication compliance in elderly TB patients. Results: Surprisingly, there was no significant increase in compliance after the intervention (p-value of 0.134). However, the X2 continuity correction analysis revealed that counseling and supervision doubled medication adherence in the elderly. Conclusions: health counseling, consisting of 30-minute sessions from diagnosis to recovery, utilizing media such as posters, is highly recommended by health workers. This intervention aims to improve medication compliance and adherence to the recommended schedule effectively.